A comparison of nonlinear vibration and bending of hybrid CNTRC/metal laminated plates with positive and negative Poisson's ratios. (1st October 2020) - Yu, Yin; Shen, Hui-Shen
Highlights: Both piece-wise functionally graded configurations and negative Poisson's ratios are considered. The material properties of both CNTRC layer and metal layer are temperature dependent. NPR has a significant effect on the nonlinear vibration behavior of hybrid CNTRC/metal plates. NPR has a significant effect on the nonlinear bending behavior of hybrid CNTRC/metal plates. Abstract: This paper reports a study on the large amplitude vibration and nonlinear bending behaviors of hybrid laminated plates made of carbon nanotube-reinforced composite (CNTRC) layers bonded with metal layer on the top surface. The hybrid CNTRC/metal laminated plates with out-of-plane negative Poisson's ratio (NPR) are proposed. The effective material properties of CNTRC layer are graded in the thickness direction in a piece-wise pattern. The material properties of both CNTRC layer and metal layer are temperature dependent. The plates are placed on an elastic foundation and in thermal environments. The Reddy's third order shear deformation plate theory is utilized to establish the motion equations of the hybrid CNTRC/metal laminated plate. These equations include the geometric nonlinearity in the von Kármán sense, the thermal effects and the plate-foundation interaction. By employing a two-step perturbation approach the nonlinear vibration and bending solutions are obtained. A comparison of nonlinear responses of hybrid CNTRC/metal laminated plates with positive and negative Poisson's ratios under different thermal environmental conditions is carried out and discussed in details. Graphical abstract: Image, graphical abstract